The Problem of Russian Reading Training for Chinese Students: State and Prospects (Proceedings of the International Conference on Future of Education, 2021)
: The article aims to discuss the main features of teaching reading in the lessons of RFL(Russian as a foreign language) in the Chinese audience. Foreign language reading is significantspeech activity because it is the basis of developing other speech activities. The article analyses thephonetical and methodological barriers, which may meet Chinese students while improving theirreading skills, and provide some methods of removing the difficulties in reading. When teachingRussian to Chinese students, especially outside the linguistic environment, teachers do not pay dueattention to practicing various types of reading, and, consequently, automating verbal forecasting. Inthe methodological literature, to overcome oral speech problems, the need to focus on spontaneousoral speech is noted, directly related to reading as a resource for expanding vocabulary andgrammatical structures. Using system analysis, comparison, typology, theoretical andmethodological forecasting, the work compares the most popular types of reading in China andRussia when teaching international students, analyzes the advantages and disadvantages of usingthese types of reading. Based on Chinese students’ most frequent difficulties, a developed balancedtype text is proposed that considers the most problematic phonetic cases. Also, a system of variousexercises is proposed, aimed at developing the skills of oral speech. The exercises and use ofphonetically balanced texts might contribute to the further enrichment of RFL methodology.
Keywords: reading technique; Chinese interference; Russian as a foreign language; words indentation